How does a collaborative network of public policies in Argentina learn? - Estévez, Alejandro M. (Journal Studies of Public Policy, 2023)
This study aims to demonstrate how learning occurs in public policy networks. These networks select problems through prior diagnosis and approach their solutions diversely. Learning takes place through interaction with the political, social, and economic context, and is strengthened through experience. Information exchange is key among similar networks, but learning also occurs through competition and criticism. Continuous reflection and the role of the coordinator are important. Networks learn by facing challenges, prioritizing learning from failures. Obstacles include power conflicts, individual interests, lack of incentives, lack of achievements, lack of a clear identity, bureaucratization, deviation from objectives, and immobility. Networks that engage in reflection, utilize technology appropriately, and collaboratively address complex problems tend to be more successful.